Science education notes. School-based assessment in science - A Caribbean perspective - King, Winston K.
This paper discusses Caribbean experiences with school-based assessment in science, considering the general education background against which the strategy was adopted, some school conditions that appeared to be critical to its implementation, and its apparent impact on the teaching and learning of science
Keywords: School-based assessment